Cultural Resonance and the Diffusion of Ngaji Lagu as Qur’anic Da‘wah Practice: Socio-Cultural Transformation in South Sumatra - M. Saiyid Mahadhir; Abdullah Idi; Muhammad Noupal (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This study examines the diffusion of Ngaji Lagu (nagham), a locally rooted Qur’anic recitation practice employing melodic patterns, and its cultural resonance within the Muslim community of Ogan Ilir, South Sumatra. Cultural resonance in this study is defined as the capacity of a religious–cultural practice to be meaningfully received, reproduced, and institutionalized across social groups, thereby shaping cultural continuity and transformation. Grounded in diffusion of innovation theory and cultural anthropology, the research aims to analyze the diffusion process of Ngaji Lagu, identify its supporting and inhibiting factors, and examine its socio-cultural and religious impacts. The study adopts a qualitative ethnographic approach conducted through prolonged fieldwork in Ogan Ilir. Data were collected through participant observation, in-depth interviews, and document analysis. Interviews involved 28 purposively selected informants, chosen based on their knowledge, mastery, understanding, and active involvement in the practice, transmission, and development of Ngaji Lagu within the Ogan Ilir community. The informants comprised Ngaji Lagu practitioners, religious scholars, educators, MTQ organizers, and community figures who play key roles in the diffusion process. Data analysis followed an interactive model of data reduction, categorization, interpretation, and verification, with trustworthiness ensured through triangulation, prolonged engagement, thick description, reflexive analysis, and peer debriefing. The findings reveal that the diffusion of Ngaji Lagu unfolded through three phases—initiation, early dissemination, and development—facilitated by pilgrimage networks (haji nahun), cultural amalgamation, and educational–competitive arenas. Diffusion occurred through informal, formal, non-formal, media, and MTQ channels, generating innovations in melodic patterns, functional orientation, and pedagogical methods. Supporting factors include the cultural authority of key diffusors, institutional support, media expansion, and strong community demand, while inhibiting factors involve uneven distribution of MTQ-standardized teachers, limited curricular integration, and declining youth engagement. Synthesizing these findings, the study proposes the Cultural Resonance Theory of Nagham (CReToN) as an analytical framework that emphasizes resonance as a mediating mechanism between religious innovation and socio-cultural transformation.